Information Asymmetry, Good Corporate Governance, and Deferred Tax Expenses Affect Earnings Management - Permatasari, Maulina Dyah; Yahya, Adibah; Andriyani, Meli; Rusdianzyah, Rully (EKOMABIS: Jurnal Ekonomi Manajemen Bisnis, 2024)
Profit control is an action taken by company management to change financial statements to make them appear more favourable to stakeholders. This is, of course, influenced by various factors, including internal factors as well as external factors. In this research, the author intends to analyse external factors using information asymmetry proxies for earnings management, while the internal factors that the author raises are corporate governance, or good corporate governance, as well as financial reports in the form of deferred tax expenses. This research aims to analyse the influence of information asymmetry, institutional ownership, size of the board of commissioners, and deferred tax burden on earnings management practices in the corporate context. This study uses financial data of companies listed on the stock exchange and performs statistical analysis to identify the relationship between the variables mentioned above and earnings management practices. The data used comes from a certain period, covering various industries. The data analysis method uses quantitative descriptive analysis, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The findings indicated that institutional ownership information asymmetry, deferred tax expense, and board size did not significantly affect earnings management, even though board size had a favourable and significant influence. The board of commissioners' size, however, has a favourable and noteworthy impact. At the same time, there is no discernible impact on earnings management from the knowledge asymmetry of institutional ownership, board size, or deferred tax expense.